Corporate Fraud and Internal Control + Software Demo : a Framework for Prevention - Cascarino, Richard E. (Hoboken : Wiley, 2012)
Essential guidance for companies to examine and improve their fraud programs Corporate governance legislation has become increasingly concerned with the ongoing resilience of organizations and, particularly, with their ability to resist corporate fraud from the lowest levels to the upper echelons of executive management. It has become unacceptable for those responsible for corporate governance to claim, ""I didn't know."" Corporate Fraud and Internal Control focuses on the appropriateness of the design of the system of internal controls in fraud risk mitigation, as well as the mechanisms to en.
Contract Implementation.
Print version record.
Keywords: Business; Auditing, Internal; Fraud -- Prevention; BUSINESS & ECONOMICS -- Accounting -- Financial; Business; Electronic books